(untitled) (Fiep Bulletin - online, 2019)
This article presents an overview of the research on burnout, emotion management and public health policies in teachersin Colombia. A systematic review of 30 scientific articles made and published between 2013 and 2018 was carried out. The databasesand search engines used were Scielo, Redalyc and Dialnet. As for the results, aspects such as the conceptualization of the constructsand meanings of the burnout syndrome, the characteristics of the people who present it are contemplated. Among the mainconclusions we point out that studies that take into account the burnout syndrome, its prevention policies and education in themanagement of emotions for teachers should be strengthened. This demonstrates the need to deepen the systemic complexity of thecondition; In addition, the need to build a model that allows the transformation in the way of addressing the issue of emotionmanagement in the processes of teacher training and teachers in practice is observed.